A Novel Method for Oblate Spherical Powder with Adjustable Combustion Property. (March 2020) - Gu, H; Ding, Y J; Xiao, Zh L; Ying, S J; Wu, W L
Abstract: In order to obtain the oblate spherical power with adjustable combustion property, a novel method was put forward combining the microporous technology and the polymer deterring technology. In this work, the oblate spherical power was foamed with the cell structure by supercritical carbon dioxide (SC-CO2 ), and then poly(neopentanediol adipate) (NA) was employed as the deterrent to modify the energy releasing rates in the surface. The combustion property of oblate spherical power under different processing conditions was investigated by the closed bomb tests. The results indicated that the microporous oblate spherical powder displayed the desired progressive combustion, and the combustion property of microporous oblate spherical powder could be adjusted by controlling the desorption time, foaming temperature, NA content, desensitization time and desensitization temperature. The spherical powder with skin-core structure foamed by SC-CO2 and deterred by NA provides a novel and promising method to realize the progressive combustion performance without dibutyl phthalate (DBP).